Pengaruh Beberapa Faktor aterhadap Produksi Industri Kerajinan Patung kayu di kecamatan Abiansemal - Deviana, Made Linda; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 7, Juli 2015 (pp.746 - 872), 2015)
The purpose of this is to determine whether the capital, work experience and technology influence either simultaneously or partially the production of the reactor timber craft industry in Abiansemal, Badung. This study using multiple regression analysis with the help of field program SPSS as the analytical method. The analysis showed that, variable capital, labor and technology experience simultaneously affect the production of wooden craft industry Abiansemal, Badung. Determination coefficient of 59.50 percent, which means the variation or the fluctuation of the timber craft industry in Abiansemal simultaneously influenced by the independent variables (capital, labor and technology experience). Partially the capital, work experience and technologi variable positive and significant effect on the production of wooden craft industry in the Abiansemal, Badung.
Keywords: Keywords capital, labor, technology, industry